Implementasi Kaidah al-Ijtihad la Yunqad bi al-Ijtihad dalam Penetapan Hukum Sesuai Hukum Islam - Fitria Nur Afifatur Rohmah; Muhammad Nuruddien (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2022)
The development in the aspect of human life era rapid, and it greatly influences the shaping of rules that dictate human behaviour. Al-Qur'an and Hadith are the primary sources of guidance for Muslims in facing their many challenges. However, the Al-Qur'an and Hadith do not contain all detailed legal provisions. Many laws in the Qur'an and Hadith are global and universal. To overcome this problem, the scholars tried to focus on ijtihad to enforce the law using Islamic legal maxims. Islamic legal maxim is a field of science that studies the rules involved in istinbat (excavation) of a syara' law. One of the rules is al-ijtihad la yunqad bi al-ijtihad related to the study of Usul Fiqh, under the term of kulliyah aghlabiyah (majoritarian-representative) norm. Ijtihad is an essential media that plays a vital role in creating Islamic law. This rule helps in solving problems in the social, economic, political, cultural and other fields. This writing aims to provide a complete picture of Islamic legal maxims and apply it in determining the law following Islamic law and legislation in Indonesia to produce legal certainty for a problem.   Abstrak: Perkembangan zaman sangat pesat sehingga sangat mempengaruhi ketentuan-ketentuan hukum sebelumnya. Al-Qur'an dan Hadits adalah sumber utama pedoman bagi umat Islam dalam menghadapi banyak tantangan mereka. Namun, di dalam Al-Qur'an dan hadits tidak terkandung semua ketentuan-ketentuan hukum secara terperinci. Banyak hukum dalam Al-Qur'an dan Hadits bersifat global dan universal. Untuk mengatasi masalah ini, para ulama berusaha untuk memfokuskan semua upaya mereka untuk ijtihad guna menegakkan hukum dengan menggunakan kaidah-kaidah fiqhiyyah. Qawa'id Fiqhiyyah adalah bidang ilmu yang mempelajari aturan-aturan yang terlibat dalam istinbat (penggalian) suatu hukum syara'. Salah satunya kaidah al-ijtihad la yunqad bi al-ijtihad adalah Dalam kajian Ushul Fiqh, terdapat norma kulliyah aghlabiyah (majoritative-representative). Ijtihad merupakan media penting yang berperan penting dalam penciptaan hukum Islam. Aturan ini membantu dalam penyelesaian masalah di bidang sosial, ekonomi, politik, budaya, dan lainnya.  Dalam penulisan ini bertujuan untuk memberikan gambaran yang utuh dan menaplikasian dalam penetapan hukum sesuai dengan hukum islam dan perundang-undangan di Indonesia untuk menhasilkan kepastian hukum suatu permasalahan.